Le programme de suivi de la pêche récréative hivernale aux poissons de fond dans le fjord du Saguenay : un effort collectif - Johanne Gauthier (Le Naturaliste canadien, 2018)
In the early 1980s, a winter recreational fishery developed for groundfish in the Saguenay Fjord (Québec, Canada). Fishers discovered a unique ecosystem harboring a wide variety of fish species, including deepwater redfish (Sebastesmentella), Atlantic cod (Gadus morhua), Greenland cod or ogac (Gadusogac) and Greenland halibut (Reinhardtiushippoglossoides). The recreational fishery and an associated tourism activity grew rapidly, with villages of fishing huts being established on the pack ice between Saint-Fulgence and L’Anse-Saint-Jean. This led to concerns among several stakeholders in the community about the conservation of fish stocks and the sustainable development of the fishery. As a result, in 1995, a monitoring program was established. This program is coordinated by Fisheries and Oceans Canada and delivered in collaboration with numerous partners, including Parks Canada and the Société des établissements de plein air du Québec (the co-managers of the Saguenay–Saint-Laurent Marine Park), local fishing associations, and Promotion Saguenay. This collective effort has highlighted significant changes in the status of groundfish populations in the Saguenay Fjord and introduced management measures aimed at protecting these resources. Au début des années 1980, une pêche récréative hivernale aux poissons de fond prend son essor dans le fjord du Saguenay (Québec, Canada). Les adeptes de cette pêche découvrent alors un écosystème unique qui recèle une grande diversité d’espèces de poissons, dont le sébaste atlantique (Sebastes mentella), la morue franche (Gadus morhua), la morue ogac (Gadus ogac) et le flétan du Groenland (Reinhardtius hippoglossoides). Des villages de pêche sont installés sur la banquise entre Saint-Fulgence et L’Anse-Saint-Jean. Cette activité récréotouristique gagne rapidement de l’ampleur, amenant plusieurs intervenants du milieu à se préoccuper de la conservation des ressources et du développement durable de cette pêche. Dans ce contexte, un programme de suivi de la pêche récréative ...